Building a copepod constraint imaging system - Aarynjeet Singh Travis (Nanyang Technological University, 2022)
Microscopes are optical instruments built to magnify objects or specimens that are too small to be seen by the naked eye. They have been widely used in a multitude of industries such as the medical and materials industry. It has allowed humans to analyze cells, material structures and diseases to a far better extent than before. With the development of the electron microscope, humans are even able to visualize objects down to the atomic level. In the current society, where most of our daily tasks are being automated and digitalized, people are now able to access information and perform tasks with much higher efficiency and productivity. The use of a microscope is an example where automation and digitalization can help to reduce time taken and give better insight into samples and specimens. It can help doctors understand diseases much quicker and easier. The purpose of this report is to design and build a prototype that automates and digitalizes a microscope which helps in reducing the time taken to position and focus a sample. It will also provide the digitalization of samples and provides convenience to the user. The design will be done using Autodesk Inventor & fabricated using a mixture of standard parts and 3D Printing. This will make the design more affordable and easier to manufacture, appealing to a wider range of people. Several prototypes were built and tested to achieve the desired outcomes. These prototypes provided a baseline for the final design which would achieve a stable and working microscope.